Can Bonus Payments Improve the Quality of Health Care? - World Bank (Washington, DC, 2012)
The goal was to see whether linking bonus payments to performance had a positive effect. Rwanda, which was forced to rebuild its institutions after the 1994 civil war and genocide, began piloting programs in 2001 to give health clinics cash bonuses for meeting certain healthcare objectives, such as immunizing children, and for encouraging people to utilize medical services, such as having pregnant women deliver in a medical facility. Rwanda's health outcomes in the areas of mother-child healthcare ranked among the worst for countries in eastern and southern Africa and the pro programs were an attempt to ensure that people, especially women and children, could get the care they needed to stay healthy.